Aerodynamic Analysis of Propeller for Heavy Lifting Drone Applications Using Blade Element Momentum Analysis - Wan Salim, Wan Saiful-Islam; bin Aminuddin, Ahyatuddin (Progress in Aerospace and Aviation Technology, 2022)
Nowadays, drone technology is seen to be rapidly advancing in various fields and applications including photography, military, transportation, sports, and many more. Therefore, each drone model may require different aerodynamic requirements, thereby requiring different types of propeller designs. By revolving and generating airflow, the propellers give drones or unmanned aerial vehicles (UAV) a lift force. This research examines the airflow characteristic and calculates the thrust force value for propellers. This investigation compares the thrust coefficient trend grafts produced by four propellers with various rotation speeds and parameters using the extended blade element momentum theory. This program is developed to perform the calculation of thrust and torque for a given propeller blade geometry. Five different types of propellers are analysed and simulated using an in-house MATLAB program. The effects of rotational speeds are then added to these databases. At low advance ratios compared to a generic blade element-momentum model, a considerable improvement in modelling accuracy is seen when results are compared to experimental ones. The calculation may overestimate performance by 5% to 10%.